Chinese environmental law / Yuhong Zhao. - Zhao, Yuhong (Cambridge University Press, 2021)
China has industrialized and urbanized at unprecedented scale and speed since its economic take-off began in the 1980s. It has become the world's second largest economy, but pollution has pushed the environment to the limits of its carrying capacity. Chinese Environmental Law provides a comprehensive and structured analysis of the increasingly sophisticated Chinese environmental legal regime. It examines the regulation of pollution in detail, covering key environmental statutes, policies and plans, and investigates judicial innovation in the interpretation and application of environmental legal instruments. The book presents Chinese environmental law in action and in context. By discussing key institutions and processes, readers will understand the operation of the environmental law and policy, the dynamic interactions between state and non-state actors, and the special challenges to the implementation and enforcement of environmental law in the socio-economic and political context of China.